Innovations in computational intelligence, big data analytics, and internet of things - Goundar, Sam, 1967-; Avanija, J.; Sunitha, Gurram; Madhavi, K. Reddy (Emerging information technologies : applications, innovations, and research, 2024)
"As sensors spread across almost every industry, the internet of things is going to trigger a massive influx of big data. We delve into where IoT will have the biggest impact and what it means for the future of big data analytics. Internet of Things is changing the face of different sectors such as manufacturing, health-care, business , education etc. by completely redefining the way people, devices and apps connect and interact with each other in the eco system. From personal fitness and wellness sensors, implantable devices to surgical robots - IoT is bringing in new tools and efficiencies in the ecosystem resulting in more integrated healthcare. Application of computational intelligence techniques is today considered as a key success factor to solve the growing scale and complexity of problems in the field of health care systems, agriculture, e-commerce etc. The convergence of Computational intelligence, Big Data and IoT provides new opportunities and revolutionize business in huge way. This book will support industry and governmental agencies to facilitate and make sense of myriad connected devices in coming decade. This book offers the recent advancements in Computational Intelligence, IoT and Big Data Analytics"--